Instalasi Perangkat Pembangkit Listrik Tenaga Surya (PLTS) Sebagai Sumber Energi Pada Taman Gedung Makhtab Kampus Panca Budi - Chandra Danova Siringo Ringo (Jurnal Teknik Mesin, Industri, Elektro dan Informatika, 2022)
Electricity is a very important need for the life of many people. Especially with the increasing number of tools that use electricity as a source of energy in this day and age. With the increasing demand for electricity, the more electrical energy that must be issued, especially by PLN. Electricity is also a source of energy that is needed in all activities related to electronics, therefore its use varies greatly. The purpose of making this final project entitled "Installation of Solar Power Generation Devices (PLTS) as a Source of Electrical Energy in the Garden of the Mahktab Building, Panca Budi Campus" is as a form of saving electrical energy in garden lighting. Electrical energy saving is done by utilizing solar cells, batteries as current storage and LED lights which are operated with a control system. The method used in this final project is the design method. The method steps are analysis, design, manufacture and testing. analysis, design, manufacture and testing. The design of the solar cell device as a converter of solar energy into electrical energy which is then stored in the battery.